The Effectiveness of Contextual Teaching and Learning in Improving Students’ Reading Comprehension - Utami, Nurhikma; Yahrif, Muhammad; Rosmayanti, Vivit; Siradjuddin, Suharti (Journal of Languages and Language Teaching, 2023)
Contextual teaching and learning is one of the outstanding approaches that can help students understand the meaning of teaching materials based on personal, social, and cultural contexts. Due to this, students can have the knowledge and skills to actively build their understanding of the materials. Therefore, this study aims to find out the effectiveness of contextual teaching and learning in improving students' reading comprehension at SMP Negeri 2 Mappakasunggu Takalar. This study involved 56 students of seventh-grade students. This study used a quasi-experimental with two classes, the experimental class, and the control class. Data was collected through a reading test that was given to students before and after giving the Contextual Teaching and Learning method. In analyzing the data, the researchers used the SPSS version 22. The results of data analysis showed that the post-test mean value was 26.04 compared to without using CTL or conventional in the control class, the post-test mean value was 23.71. In addition, the calculation results of the SPSS version 22 application showed that the value of the t-count calculation was 2.3. Compared with table df = 54, namely (2.0) the significance level was 5%, t count > t table, then Ha was accepted and Ho was rejected. In other words, accept the alternative hypothesis (Ha) and reject the null hypothesis (Ho) to test both variables. From the results of hypothesis testing, it was proven that There was a significant effect between the use of contextual learning.Â